A Single-Scan, Rapid Whole-Brain Protocol for Quantitative Water Content Mapping With Neurobiological Implications - Oros-Peusquens, Ana-Maria; Loução, Ricardo; Abbas, Zaheer; Gras, Vincent; Zimmermann, Markus; Shah, N. J. (Frontiers in Neurology, 2019)
Water content is a conceptually simple quantity, highly relevant to biological systems, which can be measured by MRI. Water concentration is tightly regulated in the healthy human brain and changes only slightly with age and gender in healthy subjects. Changes in water content are important for the characterisation of disease. As they are usually in the low percentage range, methods with very high precision and accuracy are required for detection. The method proposed here is based on a long-TR (10s) multiple-echo gradient-echo measurement with an acquisition time of 7:21 minutes. Using such a long TR ensures that there is no T1 weighting, which means that the image intensity at zero echo time is only proportional to water content, transmit field, and the receive field. The receive and transmit corrections, which are increasingly large at higher field strengths and for highly segmented coil arrays, are multiplicative and can be approached heuristically, using a bias field correction. We have tested the method on 21 healthy volunteers at 3T field strength. Calibration using cerebral-spinal fluid values ( 100% water content) results in mean values and standard deviations of the water content distribution in white matter and grey matter of 69.1% (1.7%) and 83.7% (1.2%), respectively. Measured distributions were coil-independent, as seen by using either a 12-channel receiver coil or a 32-channel receiver coil. In a test-retest investigation using 12 scans on one volunteer, the variation in the mean value of water content for different tissue types was 0.3% and the mean voxel variability 1%. The robustness against reduced SNR was assessed by comparison of 1.5T and 3T results for 5 additional volunteers. The water content distribution in grey matter is investigated and regional contrast reported for the first time. Clinical applicability is illustrated with data from one stroke patient and one brain tumour patient. It is anticipated that this fast, stable, easy to use, high-quality mapping method will open the road to routine quantitative MR imaging of water content.